The Coign Automatic Distributed Partitioning System - Hunt, Galen; Scott, Michael L. (Third Symposium on Operating System Design and Implementation (OSDI), 1999)
Although successive generations of middleware (such as RPC, CORBA, and DCOM) have made it easier to connect distributed programs, the process of distributed application decomposition has changed little: programmers manually divide applications into subprograms and manually assign those sub-programs to machines. Often the techniques used to choose a distribution are ad hoc and create one-time solutions biased to a specific combination of users, machines, and networks. We assert that system software, not the programmer, should manage the task of distributed decomposition. To validate our assertion we present Coign, an automatic distributed partitioning system that significantly eases the development of distributed applications. Given an application (in binary form) built from distributable COM components, Coign constructs a graph model of the application's inter-component communication through scenario-based profiling. Later, Coign applies a graph-cutting algorithm to partition the application across a network and minimize execution delay due to network communication. Using Coign, even an end user (without access to source code) can transform a non-distributed application into an optimized, distributed application. Coign has automatically distributed binaries from over 2 million lines of application code, including Microsoft's PhotoDraw 2000 image processor. To our knowledge, Coign is the first system to automatically partition and distribute binary applications.